Apprehension of Newborn Infants by Child Protection Services: Experiences of Mothers - Parmar, Natasha (Université d'Ottawa / University of Ottawa, 2021)
In Ontario, 1% of women who give birth have their newborn infant apprehended by child protection agencies (~200/year). Hospital-based perinatal nurses are in a unique position to support mothers. However, there is a lack of research examining mothers’ experiences of newborn infant apprehension. The purpose of this study was to explore mothers’ experiences with nurses and other providers when newborn infant apprehension occurs. Doka’s Disenfranchised Grief Framework was used as a lens to help guide the research questions, methods and analysis. Thorne’s Interpretive Descriptive approach was employed. Mothers who had experienced newborn infant apprehension in the last 10 years were recruited from an agency in Ontario. Nine individual, semi-structured interviews were conducted. When analyzing the data, the researchers identified patterns and themes from among the mothers’ varied experiences. The analysis resulted in four themes: Not good enough, I am a mother, I have rights, I live everyday like I’m grieving, and Hope in the face of adversity. The findings illuminated the imbalance of power that mothers face when experiencing newborn infant apprehension, where power and authority rest with health and social service providers. This research study will focus on the findings describing what mothers want - for nurses to be open-minded, non-judgmental, to teach mothers regarding cycles of violence, and to advocate for mothers’ rights. Ultimately, the mothers posited that nurses are well positioned to empower mothers, thereby giving them the opportunity to begin recovery. The findings indicate a need for nurses to provide safe, compassionate, competent, ethical care and inform how perinatal nurses can better support mothers experiencing newborn infant apprehension.
Keywords: Apprehension; Newborn; Custody loss; Grief; Mothers; Maternal identity; Experiences; Disenfranchised grief; Marginalized; Mothers' rights; Perinatal nurses; Child protection services; Interpretive descriptive